Analisis Kebijakan Publik Dalam Penguatan Ekowisata Berbasis Masyarakat Di Era Desentralisasi - Andriwiguna, Adhy; Genedin, Triananda; Nugraha, Budi (Prediksi : Jurnal Administrasi dan Kebijakan, 2026)
Decentralization provides opportunities for regions and villages to develop community-based ecotourism, but its implementation is still hampered by coordination, institutional capacity, and suboptimal community participation. This study aims to analyze the design and implementation of public policies in strengthening community-based ecotourism in the era of decentralization by examining the roles of regional governments, villages, and local communities. The method used is a qualitative approach through case studies of several ecotourism villages that represent various patterns of governance and community participation. Data were obtained through in-depth interviews, policy document analysis, and field observations. The results of the study indicate that strengthening community-based ecotourism is strongly influenced by three main factors: clarity of policy substance, the capacity of local actors, and patterns of collaboration between the government, communities, and other stakeholders. In addition, the success of implementation is largely determined by government support in the form of regulations, mentoring, and financing schemes that involve the community. This study concludes that strengthening community-based ecotourism requires policies that are integrative, participatory, and based on local potential. These findings are expected to serve as a reference for regional governments and tourism village managers in formulating more adaptive and sustainable policies.